2017
DOI: 10.3389/fmicb.2017.02425
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin-7-O-Glucoside Present in Lettuce Extracts Inhibits Hepatitis B Surface Antigen Production and Viral Replication by Human Hepatoma Cells in Vitro

Abstract: Hepatitis B virus (HBV) infection is endemic in Asia and chronic hepatitis B (CHB) is a major public health issue worldwide. Current treatment strategies for CHB are not satisfactory as they induce a low rate of hepatitis B surface antigen (HBsAg) loss. Extracts were prepared from lettuce hydroponically cultivated in solutions containing glycine or nitrate as nitrogen sources. The lettuce extracts exerted potent anti-HBV effects in HepG2 cell lines in vitro, including significant HBsAg inhibition, HBV replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Luteolin (3′, 4′, 5, 7‐terahydroxyflavone) is a common effective dietary flavonoid that is present in fruits, vegetables, and medicinal herbs (Liu, Xu, Yan, Cheng, & Liu, ; Song et al, ). Furthermore, accumulating evidences have suggested that luteolin possesses multiple pharmacological activities such as anti‐inflammation, anti‐hypertension, antioxidant, and antitumor, which are also supposed to be the basis of these biological properties (Aziz, Kim, & Cho, ; Cui et al, ). Previous studies indicate that luteolin suppress cancer cell growth through multiple mechanisms including promoting cancer cell apoptosis and cell cycle arrest, inhibiting cell proliferation and tumor growth, improving drug resistance, and mitigating invasiveness and metastasis of cancer cells (Cook, Liang, Besch‐Williford, & Hyder, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Luteolin (3′, 4′, 5, 7‐terahydroxyflavone) is a common effective dietary flavonoid that is present in fruits, vegetables, and medicinal herbs (Liu, Xu, Yan, Cheng, & Liu, ; Song et al, ). Furthermore, accumulating evidences have suggested that luteolin possesses multiple pharmacological activities such as anti‐inflammation, anti‐hypertension, antioxidant, and antitumor, which are also supposed to be the basis of these biological properties (Aziz, Kim, & Cho, ; Cui et al, ). Previous studies indicate that luteolin suppress cancer cell growth through multiple mechanisms including promoting cancer cell apoptosis and cell cycle arrest, inhibiting cell proliferation and tumor growth, improving drug resistance, and mitigating invasiveness and metastasis of cancer cells (Cook, Liang, Besch‐Williford, & Hyder, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Active compound, Luteolin-7- O -glucoside, extracted from leafy vegetable lettuce ( Latuca satica L. ) has been shown to significantly reduce HBsAg production (>82%; Cui et al, 2017 ). The plant extract had no cellular toxicities at lower concentrations.…”
Section: Different Classes Of Hbsag Inhibitorsmentioning
confidence: 99%
“…The plant extract had no cellular toxicities at lower concentrations. The viral RNA is a biomarker for activity of HBV transcription ( Cui et al, 2017 ). Accordingly, the viral RNA was significantly reduced (43.9%), which was consistent with reduced HBV replication ( Cui et al, 2017 ).…”
Section: Different Classes Of Hbsag Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lettuce is a significant source of many nutrients and has been reported to exert antioxidant (Yang et al, 2017), antihepatitis B virus (Cui et al, 2017), anti-inflammatory (Pepe et al, 2015), and antidiabetic (Cheng et al, 2014) effects. However, leafy vegetables, such as spinach and lettuce, represent significant sources of nitrate in the human diet, providing 40% to 92% of the average daily intake of nitrate and its metabolite nitrite (14% to 43% of daily dietary intake) (Liu et al, 2014;Qadir et al, 2017).…”
mentioning
confidence: 99%